Device for the Construction of Knowledge for a Transforming Change towards Human Development (Ágora de Heterodoxias, 2019)
This article proposes a framework for the configuration of a device for the construction of knowledge in and for action from the perspective of a democratic leadership for a transformative change towards human development. The general thesis of this approach is based on the fact that current forms of leadership training are not appropriate to bring about transformative changes in democratic and complex social environments, and are not relevant in the context of trends and digital transformation processes of governance models.
Keywords: Complexity; Change; Democracy; Development; Leadership